Ki-67 Expression is Correlated with Cyst Size and Stage of Endometriosis - Alif, Muhammad (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objectives: To analyze the association between Ki-67 expression with the cyst size and stage of endometriosis, and the correlation strength between them. Methods: A cross-sectional analytic observational study involving 56 paraffin blocks from subjects diagnosed with endometriosis, who had undergone laparotomy or laparoscopic surgery. The study is conducted in Dr. Hasan Sadikin Hospital in September-November 2012. Results: Shows a significant association between Ki-67 expression and the size of endometriotic cyst (p < 0.0001), also with a strong correlation (r = 0.55) according to Guilford criteria. There is also a significant association between Ki-67 expression and the endometriosis stage (p < 0.0001), with a strong correlation (r = 0.564) according to Guilford criteria. Conclusion: Ki-67 expression is correlated with the cyst size and stage of endometriosis. [Indones J Obstet Gynecol 2013; 1-3: 124-8] Keywords: endometriosis stage, endometriotic cyst size, Ki-67